Incidence of Positive Human Papillomavirus High Risk in Negative Cytology Result: Insidensi Kejadian Human Papillomavirus RisikoTinggi Positif pada Hasil Sitologi Negatif - Junita Indarti; Darrell Fernando; Finish Fernando; Ribkhi A. Putri; Anggara Mahardika; Muhammad Ikhsan (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective: This research aim is to report the incidence of positive HPV high risk in negative cytology result. Method: We collected 83 women underwent liquid-based cytology (LBC) and HPV DNA examination at the same time. We were using DiagCor GenoFlow Human Papillomavirus Array Test (GenoFlow), a novel HPV test based on PCR and